Long-Term Safety and Efficacy of Mirogabalin for Central Neuropathic Pain: A Multinational, Phase 3, 52-Week, Open-Label Study in Asia - Takahiro Ushida; Yoichi Katayama; Yoichi Hiasa; Makoto Nishihara; Fumihiro Tajima; Shinsuke Katoh; Hirotaka Tanaka; Takeshi Maeda; Kazunari Furusawa; Yoshihiro Kakehi; Kunika Kikumori; Masanori Kuroha (Pain and Therapy, 2023)
Abstract Introduction Central neuropathic pain (CNeP) is difficult to treat and has diverse etiology, including spinal cord injury (CNePSCI), Parkinson’s disease (CNePPD), and central post-stroke pain (CPSP). The safety and efficacy of mirogabalin have been demonstrated in short-term trials, including patients with CNePSCI. The objective of our study was to confirm the safety/efficacy of mirogabalin in patients with CNePPD and CPSP, and obtain long-term data for CNePSCI. Methods This 52-week, open-label extension of a previous randomized controlled study was conducted across Japan, Korea, and Taiwan. Patients with CNePSCI, CNePPD, or CPSP received twice daily (BID) 5–10 mg mirogabalin for a 4-week titration period, after which the dosage was maintained for 47 weeks at a maximum of 15 mg BID, followed by a 1-week taper period receiving the same dose but only administered once daily. The primary endpoint was safety, assessed primarily by incidence and severity of treatment-emergent adverse events (TEAEs). Efficacy was assessed in a post hoc analysis of data obtained by the short-form McGill Pain Questionnaire (SF-MPQ). Results Of the 210 patients enrolled, 106, 94, and 10 had CNePSCI, CPSP, and CNePPD, respectively. The mean overall age of patients was 62.9 years, and most patients were male and of Japanese ethnicity. TEAEs occurred in 84.8% of patients, the most common being somnolence (16.7%), peripheral edema (12.4%), edema (11.4%), nasopharyngitis (11.0%), and dizziness (7.6%). Most TEAEs were mild. Severe and serious TEAEs occurred in 6.2% and 13.3% of patients, respectively. All patient groups experienced reductions in SF-MPQ visual analog scores for pain: mean ± standard deviation changes from baseline at week 52 were −2.3 ± 21.13 mm (CNePSCI), −17.0 ± 24.99 mm (CPSP), and −17.1 ± 35.32 mm (CNePPD). Conclusion Mirogabalin was generally safe, well tolerated, and effective for treatment of CNeP in this long-term study. Trial registration ClinicalTrials.gov identifier, NCT03901352.